Tingkat Pengaruh Pemberian Dosis Pupuk Cair dari Limbah Dapur dan Variasi Jarak Tanam terhadap Pertumbuhan Awal Tanaman Tebu (Saccharum officinarum L.) - Sukoco, Dektiyansyah Nusantara; Junaidi; Supandji (Universitas Kadiri, 2024)
Excessive use of inorganic fertilizers is the main factor hampering the increase in sugarcane production in Indonesia. As an alternative solution, compost from municipal waste is used as organic fertilizer to stimulate the growth of sugar cane plants. This research aims to evaluate the relationship between variations in planting distance and dosage of processed kitchen waste compost products on the development of sugar cane seedlings. The research results showed that planting at a distance of 33 x 33 cm (J1) produces more optimal plant growth, including plant height, number of leaves, stem diameter, and number of tillers, compared to planting at other distances. On the other hand, administering a liquid organic fertilizer dose of 15 ml/plant (D2)gave t he best results for growth in plant height, number of leaves, stem diameter, and number of tillers. Observations on leaf area also showed that at 9 weeks after planting, planting at a distance of 33 x 33 cm (J1) had a more optimal leaf area. Giving a dose of liquid organic fertilizer of 15 ml/plant (D2) also produced optimal leaf area at that age. Root development is also influenced by variations in planting distance and the amount of liquid organic fertilizer applied. Planting at a distance of 33 x 33 cm (J1) and without applying liquid organic fertilizer (D0) resulted in better root length and number at 9 weeks after planting. The optimal combination to increase the growth of sugarcane seedlings is planting at a distance of 33 x 33 cm (J1) and applying liquid organic fertilizer of 15 ml/plant (D2). The use of organic fertilizer, such as municipal waste compost, can be a solution to reduce dependence on inorganic fertilizer and sustainably increase sugarcane production. Pemanfaatan pupuk anorganik yang terlalu banyak merupakan faktor utama yang menghambat peningkatan produksi tebu di Indonesia. Sebagai solusi alternatif, kompos dari sampah kota digunakan sebagai pupuk organik untuk merangsang pertumbuhan tanaman tebu. Tujuan dari penelitian ini adalah untuk mengevaluasi keterkaitan antara variasi jarak tanam dan dosis produk olahan kompos limbah dapur terhadap perkembangan bibit tebu. Hasil riset menunjukkan bahwa penanaman dengan jarak 33 x 33 cm (J1) menghasilkan pertumbuhan tanaman yang lebih optimal, termasuk tinggi tanaman, jumlah daun, diameter batang, dan jumlah anakan dibandingkan dengan penanaman dengan jarak lainnya. Sebaliknya, pemberian dosis pupukorganik cair sebanyak 15 ml/tanaman (D2) memberikan hasil terbaik untuk pertumbuhan tinggi tanaman, jumlah daun, diameter batang, dan jumlah anakan. Observasi terhadap luas daun juga menunjukkan bahwa pada usia 9 minggu setelah penanaman, penanaman dengan jarak 33 x 33 cm (J1) memiliki luas daun yang lebih optimal.Pemberian dosis pupuk organik cair 15 ml/tanaman (D2) juga menghasilkan luas daun yang optimal pada usia tersebut. Pengembangan akar juga dipengaruhi oleh variasi jarak tanam dan jumlah pupuk organik cair yang diberikan. Penanaman dengan jarak 33 x 33 cm (J1) dan tanpa pemberian pupuk organik cair (D0) menghasilkan panjang dan jumlah akar yang lebih baik pada usia 9 minggu setelah tanam. Kombinasi optimal untuk meningkatkan pertumbuhan bibit tebu terlihat pada penanaman dengan jarak 33 x 33 cm (J1) dan pemberian pupuk organik cair sebanyak 15 ml/tanaman (D2). Penggunaan pupuk organik seperti kompos sampah kota dapat menjadi solusi untuk mengurangi ketergantungan pada pupuk anorganik dan meningkatkan produksi tebu secara berkelanjutan.